Supporting teaching and learning in schools [ a handbook for higher level teaching assistants - Capel, Susan Anne , 1953-; Leask, Marilyn , 1950-; Younie, Sarah , 1967- (Routledge, 2009)
An accessible, user-friendly handbook designed to provide practical guidance and ideas to support Higher Level Teaching Assistants (HLTAs)